2021
DOI: 10.4081/reumatismo.2021.1312
|View full text |Cite
|
Sign up to set email alerts
|

Does human serotonin-1A receptor polymorphism (rs6295) code for pain and associated symptoms in fibromyalgia syndrome?

Abstract: Genetic predisposition may play an important role in the development of fibromyalgia syndrome (FMS). Serotonin is known to be involved in pain modulation and serotonin-1A receptor plays a considerable role in determining the central 5-HT tone. Consequently, variation in 5-HT1A receptor gene (HTR1A) may be responsible for inter-individual variability in pain sensitivity and other clinical symptoms of FMS. Therefore, the objectives of this research work were to study the gene polymorphism of 5-HTR1A gene and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It was reported that there was a significant relationship between some polymorphisms of these genes and FMS (22). However, it was found that some polymorphisms in genes encoding μ-opioid receptor gene (OPRM1) (23), human serotonin-1A receptor (5-HTR1A) (24), and beta-2 adrenergic receptor (ADRB2) were not associated with FMS (25).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there was a significant relationship between some polymorphisms of these genes and FMS (22). However, it was found that some polymorphisms in genes encoding μ-opioid receptor gene (OPRM1) (23), human serotonin-1A receptor (5-HTR1A) (24), and beta-2 adrenergic receptor (ADRB2) were not associated with FMS (25).…”
Section: Discussionmentioning
confidence: 99%
“…There's data pointing to 8.5 higher odds of familial aggregation in FM than in rheumatoid arthritis (Arnold et al, 2004) and an estimated sibling recurrence-risk ratio of 13.6 (Arnold et al, 2013). Several pain-related and non-related genes have been associated with FM (Tanwar, Mattoo, Kumar, Dada, & Bhatia, 2021), although none have been shown to consistently correlate to disease activity.…”
Section: Emerging Biomarkersmentioning
confidence: 99%
“…The involvement of 5-HT in pain modulation is of clear interest in the case of FM, considering that it is a chronic pain condition characterized by diffuse pain symptoms likely arising from deficient inhibitory conditioned pain modulation mechanisms [30]. So far, genetic studies that have examined the 5-HT 1A receptor and 5-HT 2A receptor gene polymorphisms, as well as studies measuring 5-HT blood levels, have produced mixed results [31][32][33]. In the case of the SERT, two genetic studies (one PET study and one study on gene expression) have also produced mixed results [34,35].…”
Section: Introductionmentioning
confidence: 99%